JUSTICE INTRODUCTION IN LAND LAW - syamsuddin pasamai (PRANATA HUKUM, 2022)
Justice is one of the legal goals to be realized, while the existence of land is an essential human need whose regulations need to be regulated transparently in land law. This phenomenon, ex officio places land as an integral part of human rights that must be fulfilled for the benefit and certainty of other legal purposes. Therefore, the proposed "prasaran" in Indonesian means a description of the opinion (postulate, etc.) as anintroduction to discuss or discuss a problem. The infrastructure contains the value of justice in land law regardless of the benefits and legal certainty. Ideally, land law is not static, but always dynamic by considering each individual as a member of society.